Handbook of Plant Growth : pH as the Master Variable - Rengel, Zdenko (New York : Marcel dekker, 2002)
Explores the molecular, biochemical, functional, structural, and developmental mechanisms of pH in plant growth. Examines the role of pH in plant symplasm, plant apoplasm, thr rhizosphere, the ecosystem, and plant interaction with biotic snd abiotic environments.
Includes Index 427-446p.
Keywords: Plant growth; Botany